Vertical Canopy Profile and the Impact of Branches on Soybean Seed Composition - Moro Rosso, Luiz Henrique; de Borja Reis, André Froes; Ciampitti, Ignacio Antonio (Frontiers in Plant Science, 2021)
Soybean [Glycine max (L.) Merr.] seeds are of global importance for human and animal nutrition due to high protein and oil concentrations, and complete amino acid (AA) and fatty acid (FA) profiles. However, a detailed description of seed composition at different canopy portions (i.e., main stem and branch nodes) is currently lacking in scientific literature. This study aims to 1) characterize seed yield and composition (protein, oil, AA, and FA) at the main stem (exploring a vertical canopy profile) and stem branches; and 2) quantify the impact of canopy yield allocation on seed composition, focusing on branches as potential contributor for higher yields. Four genotypes were field-grown during the 2018 and 2019 seasons, with seeds manually harvested from all the branches and three main stem segments (lower, middle, and upper). Seed samples were analyzed for seed yield (Mg ha−1), seed size (mg seed−1), protein and oil content (mg seed−1) and their respective concentrations (g kg−1), and AA and FA concentrations within protein and oil (g 100 g−1), herein called abundance. The upper main stem produced greater protein (25%) and oil (15%) content relative to the lower section; however, oil concentration increased from top to bottom while protein concentration followed opposite vertical gradient. Limiting AA (lysine, cysteine, methionine, threonine, and tryptophan) were more abundant in the lower main stem, while the oleic / (linoleic + linolenic) ratio was greater in the upper segment. Overall, branches produced seeds with inferior nutritional quality than the main stem. However, the contribution of branches to yield (%) was positively related with limiting AA abundance and oil concentration across soybean genotypes. Future research should consider the morphological process of stem branching as a critical factor intimately involved with soybean seed composition across environments, genotypes, and management practices.